Development of Mobile Health EPDS for Early Detection of Postpartum Blues for Postpartum Mothers at The Working Area of Puskesmas Sentani, Jayapura Regency - Handayani, Endah Purwanti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Postpartum mothers who cannot adapt to their new role as parents or have no family support can experience psychological (mental) disorders, namely postpartum blues, postpartum depression, and even postpartum psychosis. The purpose of this study was to develop MHEPDS for early detection of postpartum blues. Subjects and Method: Research and Development (R&D) & quasi-experimental research was conducted on postpartum mothers in the work area of the Sentani Health Center, Jayapura Regency from May 2022 to July 2022. A sample of 30 postpartum mothers was selected by simple random sampling. The dependent variable is mobile health EPDS. The independent variable is the EPDS scale. Other data collected by questionnaire. Data were analyzed by analyzing paired sample T test using the Stata 13 application. Results: Based on the results of the feasibility test of the MHEPDS application by psychologists, media and midwives for the design aspect the figure was 89.33% and for the clarity of information aspect it was 82.67%. For scores ranging from 81-100%, it is declared very feasible. The paired samples T test showed no difference between MHEPDS (Mean=15.2; SD=6.70) and EPDS (Mean=14.9; SD=6.52), and this result was not statistically significant (p= 0.662). Conclusion: The MHEPDS application has been made and can be used to detect postpartum blues events. The feasibility test for the application is declared feasible and can be used in postpartum mothers. Keywords: postpartum blues, EPDS, MHEPDS, research and development Correspondence: Endah Purwanti Handayani, Jayapura College of Health Sciences. Jl. Youmakhe Kelurahan Hinekombe Sentani 99352, Papua. Email: kakaendahmanise@gmail.com. Mobile: 085254440490.